Supervisi Korektif untuk Menemukan Kekurangan – Kekurangan Guru Kelas dalam Malaksanakan Pembelajaran di SD Negeri 173105 Tarutung - Tampubolon, Junikaya (Attractive : Innovative Education Journal, 2020)
The purpose of this article was to find the shortcomings of teachers’ class in carrying out learning State of Elementary School (SDN) 173105 Tarutung, Tarutung District. This research was a qualitative field study with descriptive approach. The target of this research was the the teachers’ class at SDN 173105 Tarutung. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. The results of analysis found that in the initial cycle of research: the teacher still had shortcomings in carrying out learning. Some of these errors such as old lesson plans were still used by the teachers, learning that is not in accordance with planning, lack of resources and learning media, and conventional learning models. Furthermore, the researchers conducted guidance in an effort to overcome teacher shortcomings. In the final cycle the teacher shortages overcome very well. From this research, it was concluded that the implementation of collaborative supervision was very effective in finding teacher shortcomings in learning, hence improvements can be made (revised). Keywords: Corrective Supervision, Teacher Quality, Learning Activity